Political Communication Cultures in Western Europe Attitudes of Political Actors and Journalists in Nine Countries - Pfetsch, B.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book offers new and compelling insight into the orientations that shape the cultures of political communication in nine Western democracies. It is a truly comparative account of the views of 2500 political elites and media elites between Helsinki and Madrid on their relationship and their exchanges.
Keywords: European Union; Communication; Europe—Politics and government; Culture—Study and teaching; Democracy; European Union Politics; Media and Communication; European Politics; Cultural and Media Studies, general; Media Studies; Democracy